2021
DOI: 10.3390/polym13162766
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Branched Polyethyleneimine Using Mesquite Gum for Its Improved Hemocompatibility

Abstract: In the present study, the modification of branched polyethyleneimine (b-PEI) was carried out using mesquite gum (MG) to improve its hemocompatibility to be used in biomedical applications. In the copolymer synthesis process (carboxymethylated mesquite gum grafted polyethyleneimine copolymer (CBX-MG-PEI), an MG carboxymethylation reaction was initially carried out (carboxymethylated mesquite gum (CBX-MG). Subsequently, the functionalization between CBX-MG and b-PEI was carried out using 1-ethyl-3-(3-dimethylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…However, at final OA concentrations of 4 and 8 mM, NP OA displayed hemolysis percentages of 78% and 100%, respectively, which may be attributed to the cytotoxicity of PEI. Due to their high density of primary amino groups, PEI or PEI-modified nanoparticles are positively charged, which gives rise to nonspecific binding to negatively charged cell membranes and severe cytotoxicity. , Neutralizing the surface amine groups to diminish the positive surface potential of particles has been a generally applied strategy to resolve the above deficiencies. Thus, RVG29-H-NP OA showed better hemocompatibility than NP OA , owing to the negative charged cell membrane wrapped on its surface that could neutralize most of the positive charges. When the final OA concentration reached 4 mM, the hemolysis percentage of the RVG29-H-NP OA was still less than 5%, and even at a final OA concentration of 8 mM, RVG29-H-NP OA did not display complete hemolysis.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, at final OA concentrations of 4 and 8 mM, NP OA displayed hemolysis percentages of 78% and 100%, respectively, which may be attributed to the cytotoxicity of PEI. Due to their high density of primary amino groups, PEI or PEI-modified nanoparticles are positively charged, which gives rise to nonspecific binding to negatively charged cell membranes and severe cytotoxicity. , Neutralizing the surface amine groups to diminish the positive surface potential of particles has been a generally applied strategy to resolve the above deficiencies. Thus, RVG29-H-NP OA showed better hemocompatibility than NP OA , owing to the negative charged cell membrane wrapped on its surface that could neutralize most of the positive charges. When the final OA concentration reached 4 mM, the hemolysis percentage of the RVG29-H-NP OA was still less than 5%, and even at a final OA concentration of 8 mM, RVG29-H-NP OA did not display complete hemolysis.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Researchers created a novel copolymer (carboxymethylated mesquite-gum-grafted polyethyleneimine (CM-MQG-g-PEI)) [ 91 ]. Initially, MQG carboxymethylation was carried out to form carboxymethylated mesquite gum (CM-MQG).…”
Section: Derivatives Of Carboxymethylated Gums (Cmgs)mentioning
confidence: 99%
“…The outcomes demonstrated nonhemolytic properties at doses less than 0.1 µg/mL (CBX-MG-PEI). The copolymer’s physicochemical and hemocompatibility potentials render it useful in formulating nanoparticles, transfection, and biomaterials [ 91 ].…”
Section: Applications Of Derivatized Carboxymethylated Gumsmentioning
confidence: 99%
“…The sulfate esters of fucoidan (representing a weak fraction of carbohydrates) may be identified by bands at 1260–1195 cm −1 (ν(S=O)). In the case of the interactions of PEI with Mesquite Gum (MG, which also bears carboxylic groups), Pinilla-Torres et al [ 92 ] reported a series of bands representing the typical bands associated with PEI and carboxylic functions from the MG: 3420 cm −1 : ν(N-H) primary amine 3280 cm −1 : ν(N-H), primary amine and Amide A band 1648 cm −1 : ν(C=O)/ν(C-N), Amide I band 1551 cm −1 : ν(N-H) primary in-plane δ(N-H)/ν(C-N)/ν(C-C), Amide II band 1241 cm −1 : ν(C-N)/δ(N-H), Amide III band 1074 cm −1 : ν(C-N) Table A1 summarizes the main peaks appearing on the spectra of the sorbents before and after Sr(II) sorption, and after the fifth cycle of desorption (to evaluate the potential degradation of the sorbents). The sorbents show a broad band at 3430–3420 cm −1 , which is assigned to the overlapping of ν(N-H) and ν(O-H), while the bands at 2950–2930 cm −1 correspond to ν(C-H).…”
Section: Appendix A1 Sem and Sem-edx Characterizationsmentioning
confidence: 99%
“…The sulfate esters of fucoidan (representing a weak fraction of carbohydrates) may be identified by bands at 1260–1195 cm −1 (ν(S=O)). In the case of the interactions of PEI with Mesquite Gum (MG, which also bears carboxylic groups), Pinilla-Torres et al [ 92 ] reported a series of bands representing the typical bands associated with PEI and carboxylic functions from the MG: 3420 cm −1 : ν(N-H) primary amine 3280 cm −1 : ν(N-H), primary amine and Amide A band 1648 cm −1 : ν(C=O)/ν(C-N), Amide I band 1551 cm −1 : ν(N-H) primary in-plane δ(N-H)/ν(C-N)/ν(C-C), Amide II band 1241 cm −1 : ν(C-N)/δ(N-H), Amide III band 1074 cm −1 : ν(C-N) …”
Section: Appendix A1 Sem and Sem-edx Characterizationsmentioning
confidence: 99%